THE INSTRUMENT OF DOIRA AND ITS ROLE IN PUBLIC LIFE - Ismail Rustamov (Galaxy International Interdisciplinary Research Journal, 2023)
This article provides opinions and comments on the functions of the musical instrument doira in the social life of the Uzbek people. A chronological description of this topic from antiquity to the present day is also given.